2013
DOI: 10.1097/dbp.0b013e31828c5fa6
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Childhood Cancer

Abstract: There are specific and identifiable impacts of childhood cancer on patients' HRQoL that are significant and complex across the span of the illness. There is a need for continued research in many areas related to this population, especially related to those with terminal illness in order to improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
3
26
0
2
Order By: Relevance
“…This may hamper the correct identification of patients with important cancer‐related fatigue. The somewhat conflicting results between the self‐reports and the parent‐proxies that were found in this study, is a phenomenon that is often encountered in pediatric psychosocial research . There is often lower agreement on subjective outcomes, such as cancer‐related fatigue, compared with more objective outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…This may hamper the correct identification of patients with important cancer‐related fatigue. The somewhat conflicting results between the self‐reports and the parent‐proxies that were found in this study, is a phenomenon that is often encountered in pediatric psychosocial research . There is often lower agreement on subjective outcomes, such as cancer‐related fatigue, compared with more objective outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Patient symptoms often go undetected during typical clinic interviews, and clinicians may underestimate the impact of symptoms from interview alone. [8][9][10] The impact of cancer and cancer treatment on patient health status can be systematically quantified using PRO measures in children and adults.…”
Section: Pros Systematically Quantify Patient Experiencesmentioning
confidence: 99%
“…[8][9][10] The impact of cancer and cancer treatment on patient health status can be systematically quantified using PRO measures in children and adults. 5,11,12 Use of PROs in these populations has identified symptoms and impairments in patient function. Most patients receiving treatment experience decreased health status 13,14 ; however, cancer patients with better symptom management and better PROs live longer with less distress.…”
Section: Pros Systematically Quantify Patient Experiencesmentioning
confidence: 99%
“…In this review the distress was different in different phases of the illness; for example the wellbeing increased over time, but it often took a long time. Fakhre et al [37] carried out a literature review on quality of life from diagnosis to remission/survivorship and end of life for children with cancer. They found that those who are newly diagnosed with cancer and undergo treatment, or are terminally ill, have impaired health-related quality of life (HRQoL).…”
Section: Discussionmentioning
confidence: 99%